Pengaruh Metode Pembelajaran terhadap Hasil Belajar Matematika pada Siswa SD Negeri 1 Gresik Kelas IV - Shifa Yuliana Sabitafh; Afakhrul Masub Bachtiar (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This research was conducted with the aim of analyzing the influence of teaching methods on mathematics learning outcomes in class IV students at SD Negeri 1 Gresik. The problem raised is the lack of understanding of mathematical concepts among students which is caused by less interesting learning methods. The research method used was a quantitative and qualitative design, with a sample consisting of 30 students selected randomly. Data was collected through mathematics learning outcomes tests and analyzed using statistical analysis to determine the significance of the influence of learning methods. The research results show that the use of active learning methods, such as picture collaboration, guided learning at home, and text learning, can significantly improve students' mathematics learning outcomes. Students who engage in active learning show better understanding and higher test scores compared to conventional methods. Future prospects, this research can be a reference for developing more innovative and effective learning methods in improving the quality of mathematics education in elementary schools. The conclusion of this research is that mathematics teachers should apply student-centered teaching methods and facilitate student participation in learning activities.